Estudio de factibilidad para el desarrollo de un s.i para el control y gestión de los bomberos compañía Babahoyo - Cortez Martinez, Ariana Caroline (2019)
Technology is currently used by most companies, whether public or private, thanks to the enormous progress that it brings, it improves management in institutions, although there are still companies and institutions that handle information manually, That is why the feasibility study was carried out for the development of an SI for the control and management of the firefighters company Babahoyo, this research aims to optimize the information that this institution manages, through a technical, operational and feasibility study economic in the fire department Babahoyo company, in order to analyze the results obtained following the line of systems research (Development of Information and Communication Systems) and the subline (Development of Computer Systems)